Can an Integrative Care Approach Improve Physical Function Trajectories after Orthopaedic Trauma? A Randomized Controlled Trial. Issue 4 (April 2020) - Zdziarski-Horodyski, Laura; Vasilopoulos, Terrie; Horodyski, MaryBeth; Hagen, Jennifer E.; Sadasivan, Kalia S.; Sharififar, Sharareh; Patrick, Matthew; Guenther, Robert; Vincent, Heather K.
Abstract: Background: Orthopaedic trauma patients frequently experience mobility impairment, fear-related issues, self-care difficulties, and work-related disability [12, 13 ]. Recovery from trauma-related injuries is dependent upon injury severity as well as psychosocial factors [2, 5 ]. However, traditional treatments do not integrate psychosocial and early mobilization to promote improved function, and they fail to provide a satisfying patient experience. Questions/purposes: We sought to determine (1) whether an early psychosocial intervention (integrative care with movement) among patients with orthopaedic trauma improved objective physical function outcomes during recovery compared with usual care, and (2) whether an integrative care approach with orthopaedic trauma patients improved patient-reported physical function outcomes during recovery compared with usual care. Methods: Between November 2015 and February 2017, 1133 patients were admitted to one hospital as orthopaedic trauma alerts to the care of the three orthopaedic trauma surgeons involved in the study. Patients with severe or multiple orthopaedic trauma requiring one or more surgical procedures were identified by our orthopaedic trauma surgeons and approached by study staff for enrollment in the study. Patients were between 18 years and 85 years of age. We excluded individuals outside of the age range; those with diagnosis of a traumatic brain injury [28 ]; those who were unable to communicate effectively (for example, at a level where self-report measures could not be answered completely); patients currently using psychotropic medications; or those who had psychotic, suicidal, or homicidal ideations at time of study enrollment. A total of 112 orthopaedic trauma patients were randomized to treatment groups (integrative and usual care), with 13 withdrawn (n = 99; 58% men; mean age 44 years ± 17 years). Data was collected at the following time points: baseline (acute hospitalization), 6 weeks, 3 months, 6 months, and at 1 year. By 1-year follow-up, we had a 75% loss to follow-up. Because our data showed no difference in the trajectories of these outcomes during the first few months of recovery, it is highly unlikely that any differences would appear months after 6 months. Therefore, analyses are presented for the 6-month follow-up time window. Integrative care consisted of usual trauma care plus additional resources, connections to services, as well as psychosocial and movement strategies to help patients recover. Physical function was measured objectively (handgrip strength, active joint ROM, and Lower Extremity Gain Scale) and subjectively (Patient-Reported Outcomes Measurement Information System-Physical Function [PROMIS®-PF] and Tampa Scale of Kinesiophobia). Higher values for hand grip, Lower Extremity Gain Scale (score range 0-27), and PROMIS®-PF (population norm = 50) are indicative of higher functional ability. Lower Tampa Scale of Kinesiophobia (score range 11-44) scores indicate less fear of movement. Trajectories of these measures were determined across time points. Results: We found no differences at 6 months follow-up between usual care and integrative care in terms of handgrip strength (right handgrip strength β = -0.0792 [95% confidence interval -0.292 to 0.133]; p = 0.46; left handgrip strength β = -0.133 [95% CI -0.384 to 0.119]; p = 0.30), or Lower Extremity Gain Scale score (β = -0.0303 [95% CI -0.191 to 0.131]; p = 0.71). The only differences between usual care and integrative care in active ROM achieved by final follow-up within the involved extremity was noted in elbow flexion, with usual care group 20° ± 10° less than integrative care (t [27] = -2.06; p = 0.05). Patients treated with usual care and integrative care showed the same Tampa Scale of Kinesiophobia score trajectories (β = 0.0155 [95% CI -0.123 to 0.154]; p = 0.83). Conclusion: Our early psychosocial intervention did not change the trajectory of physical function recovery compared with usual care. Although this specific intervention did not alter recovery trajectories, these interventions should not be abandoned because the greatest gains in function occur early in recovery after trauma, which is the key time in transition to home. More work is needed to identify ways to capitalize on improvements earlier within the recovery process to facilitate functional gains and combat psychosocial barriers to recovery. Level of Evidence: Level II, therapeutic study.